The logic of cruelty and forced disappearances in Mexico (Andamios, Revista de Investigación Social, 2022)
The article proposes to discuss the scope of the moral discourse of the logic of cruelty in forced disappearances during the six-year administration of Felipe Calderón. It also seeks to identify practices that can reverse this grammar. To this end, two perspectives are used: a philosophical-anthropological one and a political-journalistic one, whose methodological structure posits four analytical axes. These include the ethical and moral distinction to determine what the logic of cruelty involves; a political-journalistic analysis to contextualize Calderón’s “war on drug trafficking,” a turning point in the increase in forced disappearances; the instrumentality of moral grammar and the logic of criminalization in the process of forced disappearance; and the ethical response of the “searchers” that points to the transgression of the logic of cruelty.
Keywords: damaged lives; ethics; logic of cruelty; moral grammar; Forced disappearances